The relationship between preoperative serum immunoglobulin levels and the development of bacteremia after tonsillectomy. - Keleş, Erol; Gök, Uzeyir; Aral, Murat; Alpay, H Cengiz (My University, 2004)
OBJECTIVES: We examined the risk for the development of bacteremia during tonsillectomy and evaluated the presence of an association between bacteremia and preoperative serum immunoglobulin levels. PATIENTS AND METHODS: The study included 40 patients (16 males, 24 females; mean age 16.8 years; range 5 to 35 years) who underwent tonsillectomy with the use of the dissection-snear technique. Preoperatively, venous blood samples were collected from all the patients to determine serum immunoglobulin levels and the presence or absence of bacteremia. Bacteremia was also investigated in blood samples postoperatively. RESULTS: There was no growth in the preoperative blood cultures, but bacteremia was documented in 10 patients (25%) after tonsillectomy. Increased serum IgG levels were determined in 15 patients before operation, seven of whom developed bacteremia after tonsillectomy (p<0.05). There was no correlation between postoperative bacteremia and preoperative serum IgM or IgA levels (p>0.05). CONCLUSION: Although our current knowledge does not allow to predict bacteremia following tonsillectomy in advance, the finding that seven of 10 patients who developed bacteremia had increased preoperative IgG levels draws attention to serum IgG, especially in patents in whom bacteremia may present additional risks.
Keywords: Adolescent; Adult; Antibodies, Monoclonal; Bacteremia; Child; Child, Preschool; Female; Humans; Immunoglobulin G; Male; Postoperative Complications; Predictive Value of Tests; Preoperative Care; Tonsillectomy; diagnostic agent; immunoglobulin G; monoclonal antibody; adolescent; adult; article; bacteremia; blood; child; evaluation; female; human; male; microbiology; postoperative complication; prediction and forecasting; preoperative care; preschool child; tonsillectomy